Children's Rights In The Context Of Child Marriage In Gorontalo Province - Lahaling, Hijrah; Lasori, Siti Alfisyahrin; Makkulawuzar, Kindom; Yunus, Yudin; Salam, Safrin (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The practice of child marriage is quite common and is rife in Gorontalo Province. From 2019 to 2021, there were 1,383 data on applicants for child marriage dispensation at the Religious Courts of the Gorontalo Province Regency/City.Purposes of the Research: To complement the shortcomings of previous studies that did not pay attention to legal protection against neglect of children's rights in line with the increasing age of child marriage in terms of the perspective of children's rights.Methods of the Research: This study uses empirical legal research using a statutory approach, a case approach, and a conceptual approach. sources of data using primary and secondary data. Data collection techniques using literature review techniques and interviews Data analysis uses qualitative data analysis, which is analyzed theoretically to obtain prescriptive legal solutions. Results of the Research: The neglect of children's rights in cases of child marriage is more due to the unavailability of legal protection that guarantees the fulfillment of children's human rights and the legitimacy aspect of customs, culture, and traditions regarding social status in society